Bacterial Isolates from Urinary Tract Infection in Dogs and Cats in Portugal, and Their Antibiotic Susceptibility Pattern: A Retrospective Study of 5 Years (2017-2021) - Andreia Garcês; Ricardo Lopes; Augusto Silva; Filipe Sampaio; Daniela Duque; Paula Brilhante-Simões (MDPI AG, 2022)
There are growing concerns regarding the rise of antimicrobial-resistant bacteria in companion animals. This study aimed to bring new insights into the current scenario of Portugal's antimicrobial resistance bacteria isolated from companion animals with urinary tract infections and is the first to be performed during a long period on a large scale. Of a total of 17472 urine samples analyzed, 12,166 (69.6%) (CI 12,200-12,200) were negative for bacterial growth, and 5306 (30.4%) (95% CI 5310-5310) had bacterial growth. Of the culture-positive samples, 5224 (96.6%) (95% CI 5220-5220) were pure cultures and 82 (3.2%) (95% CI 81.9-82.1) had mixed growth. Escherichia coli was the most frequently isolated bacteria (n = 2360, 44.5%) (95% CI 2360-2360), followed by Proteus mirabilis (n = 585, 11%) (95% CI 583-583), Enterococcus faecium (n = 277, 5.2%) (95% CI 277-277) and Staphylococcus pseudintermedius (n = 226, 4.3%) (95% CI 226-226). The overall susceptibility rates were low for erythromycin (45.3%) and clindamycin (51.3%), and high for aminoglycosides (96.3%), carbapenems (92.4%), trimethoprim-sulfamethoxazole (81.2%), and quinolones (79.9%). E. coli also showed considerable resistance to amoxicillin-clavulanic acid. The rates of multidrug-resistant bacteria are still high compared to the northern countries of Europe. This study's findings show the emergence of antibiotic resistance in the antibiotic agents commonly used in the treatment of UTIs in dogs and cats in Portugal.